2013
DOI: 10.1080/00914037.2013.830251
|View full text |Cite
|
Sign up to set email alerts
|

Heteroarm Star-Shaped Poly (N-isopropylacryamide-co-itaconic acid) Copolymer Prepared by Glucose Core as ATRP Initiator

Abstract: Star-shaped temperature-and pH-sensitive poly (N-isopropylacryamide-co-itaconic acid) copolymer is synthesized by atom transfer radical polymerization (ATRP) using 1,2,3,4,6-penta-O-Isobutyrylbromide-a-D-glucose as 5-Arm ATRP Initiator. For ATRP of itaconic acid (IA), carboxylic groups of IA are protected via silylation by hexamethyldisilazane (HMDS) using Fe 3 O 4 as a magnetic catalyst. The polymerization is carried out in 2-propanol=toluene 50:50 (v=v) mixed solvent at 90 C. Structure of copolymers is studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Stimuli-responsive hydrogels response to environmental signals such as temperature, pH, ionic strength, and electric and magnetic fields [5][6][7]. Among the stimuli-responsive hydrogels, the poly(N-isopropylacrylamide) (PNIPAAm) based hydrogel sphere is the most popular temperature-responsive because it exhibits thermally reversible shrinkage or collapse above the lower critical solution temperature (LCST) in water [8][9][10][11] When the PNIPAAm based nanoparticles are used as drug carriers, the released drug amount could be autocontrolled by external temperature changes to significantly improve the curative effect and=or eliminate the side effect of the applied drug [12]. However, the PNIPAAm hydrogel is not a favored matrix for biomedical applications because of its transition temperature, lack of bioactivity and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive hydrogels response to environmental signals such as temperature, pH, ionic strength, and electric and magnetic fields [5][6][7]. Among the stimuli-responsive hydrogels, the poly(N-isopropylacrylamide) (PNIPAAm) based hydrogel sphere is the most popular temperature-responsive because it exhibits thermally reversible shrinkage or collapse above the lower critical solution temperature (LCST) in water [8][9][10][11] When the PNIPAAm based nanoparticles are used as drug carriers, the released drug amount could be autocontrolled by external temperature changes to significantly improve the curative effect and=or eliminate the side effect of the applied drug [12]. However, the PNIPAAm hydrogel is not a favored matrix for biomedical applications because of its transition temperature, lack of bioactivity and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that incorporation of more hydrophilic moieties (e.g., itaconic acid) with PNIPAAm hydrogel can literally bestow pH sensitivity and enhance the LCST of PNIPAAm hydrogel. 18 …”
Section: Environmentally Sensitive Hydrogelsmentioning
confidence: 99%
“…Zhang et al [18] and Saleh-Ghadimi et al [19] had reported the synthesis via RAFT polymerization of tadpoleshaped organic/inorganic hybrid POSS-containing poly(acrylic acid). Wang et al [20] had reported the synthesis of core-shell particles by batch emulsion polymerization of styrene and octavinyl-POSS.…”
Section: Introductionmentioning
confidence: 99%